PHRASEOLOGISM AND IDIOMS (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This article explores the nature, classification, and stylistic functions of phrases and idioms within the modern linguistic framework. It examines the semantic stability and cultural significance of fixed expressions, highlighting the subtle distinctions between "phraseology" as a broad field and "idioms" as specific figurative constructs. Through a comparative approach, the research analyzes how these units reflect national identity and mentalities. The findings suggest that mastering idiomatic expressions is crucial for achieving high-level communicative competence and cross-cultural understanding.